Effects of a high intensity interval session on mucosal immune function and salivary hormones in male and female endurance athletes - Monje, C.; Rada, I.; Castro-Sepulveda, M.; Peñailillo, L.; Deldicque, L.; Zbinden-Foncea, H. (Journal of Sports Science & Medicine, 2020)
Although the effects of high intensity interval training (HIIT) on health and sports performance are well documented, the effects of this training type on mucosal immune function remain unclear. The aim of this study was to assess the impact of an acute HIIT session on salivary immune and endocrine marker levels (immunoglobulin A (sIgA), alpha amylase (sAA), cortisol (C), and testosterone (T)) in male and female endurance athletes. Twenty subjects (ten males and ten females) underwent ten bouts of treadmill running using a 4 min:2 min work:rest ratio at ~90% of peak oxygen uptake (VO2peak). Saliva samples were collected 5 min before and 20 min post-exercise. During work intervals, female participants had a higher HR than male participants (+4.0 ± 5%; p = 0.008). Rating of perceived exertion (RPE) increased throughout the duration of the HIIT session in both males and females (main time effect: p < 0.001), but was higher in males than females (+17 ± 4%; time x gender main effect: p < 0.001). Lactate concentrations were similar in both males and females. Exercise increased the concentration of salivary IgA (males: +24 ± 6%, p = 0.004; females: +27 ± 3%, p = 0.03), salivary alpha-amylase (males: +44 ± 22%, p = 0.036; females: +71 ± 26%, p = 0.026) and salivary cortisol (males: +41 ± 24%, p = 0.015; females: +55 ± 24%, p = 0.005). Testosterone levels and the Testosterone/Cortisol ratio remained stable in both males and females. These findings suggest that the physiological stress produced by a HIIT session does not affect immune function and does not disturb the anabolic/catabolic balance.